Avaliação da resistência ao cisalhamento do poliestireno expandido (EPS) com interfaces de geomembranas por meio do ensaio de cisalhamento direto - Garcia, Ana Júlia da Silva (2023)
This work aims to evaluate the interface shear resistance parameters (adhesion and friction angle), resulting from the peak and post-peak resistance envelopes and the stressdisplacement behavior in different interface configurations between expanded polystyrene (EPS) and polymeric geomembranes. through direct shear tests. This study is fundamental mainly for analyzing the feasibility of using EPS blocks in geotechnical works and studying their applications. To this end, a comparative analysis was carried out between the tensions, specific mass, adhesion and friction angle of the interfaces, and a subsequent comparison with data from existing literature. Standard dimension direct shear tests (100x100 mm box) were carried out using 2 different geotechnical materials: EPS in five specific masses (10, 14.5, 18, 28 and 33.5 kg/m³) and three types of HDPE (high-density polyethylene) geomembranes: one smooth and two textured with a core thickness of 1.5 mm, the textured ones being double-sided. The main results show that the values obtained for peak and postpeak stress varied between 24º and 35º and from 15º to 34º for the textured geomembrane; 16º and 20º and from 7º to 18º for the smooth geomembrane, for peak and post-peak stress, respectively; all with zero membership fees. The shear strength at the EPS-Geomembraneinterface increased with density, except for the smooth geomembrane. The best t performance in terms of resistance was obtained for the interface with balloon matrix textured geomembrane followed by flat matrix. In comparison with the literature, the values obtained were validated, complementing the existing characterization in terms of resistance was obtained for the interface with balloon matrix textured geomembrane followed by flat matrix. In comparison with the literature, the values obtained were validated, complementing the existing characterization.